Renal hydatid disease mimicking as renal calculi in a child- A rare presentation - Meher Kalsi; Ram Mohan Shukla; Shashi Shankar Sharma; Maneesh Kumar Joleya; Ashok Kumar Ladda; Pooja Tiwari; Vinod Raj; B.K. Lahoti (Elsevier, 2022)
Hydatid disease is a common ailment requiring surgical intervention which mostly affects liver [65%] and lungs [25%], but can rarely occur in brain, bones, spleen, muscles and kidneys. In children, however, renal involvement is even rarer, constituting only 1.9% of all cases. One such very rare case presented to our institute. A 2 year old child presented with complaints of pain abdomen and whitish discharge during micturition accompanied with fever since 5 months. CT (Computed Tomography) Urography was suggestive of bilateral hydronephrosis with right staghorn calculus and left upper ureteric calculus. Surprisingly on exploration of right renal pelvis, cyst like material which looked like hydatid was found and the cortex was normal. The cysts were carefully removed and sent for histopathological examination which confirmed diagnosis of renal hydatid cysts. The patient was discharged on oral anti helmintics and is on regular follow up and doing well. The aim of this case report is to highlight that even one of the most relied upon investigations -- radiological examination can miss the diagnosis of renal hydatid and misdiagnose it as renal stones. Thus, renal hydatid disease must be kept in mind in a child having whitish discharge in urine, especially in countries like India where it is an endemic.